Konsep Pendidikan Integratif - Abd. Basit (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2023)
In the literature of Islamic scientific studies it is difficult to find differences and separation between religious knowledge and general science. Both must be studied because they need each other in building society. History records that Islam has experienced the glory of a high civilization of science with various competences in scientific disciplines and figures for centuries. This phenomenon occurred because at that time there was no dichotomy between religion and general science. Many of the works and findings of integrative education figures were transferred to other nations by way of scientific recognition. This phenomenon took place because the separation of the two sciences had taken place. There is an expression that what is obligatory to learn is only religious knowledge, while it is not obligatory for general knowledge. The reason for this is, among other things, the rapid development of knowledge, even in one scientific discipline giving rise to new knowledge. On the other hand, especially the Islamic leaders were so happy with the glittering life of the palace. Other facts emerge that many understand leaving the world, focusing on the afterlife. This opportunity is used by the western world which incidentally is not happy to see the glory of Islam. They took over the glory of Islamic knowledge in an unsatisfied way, they even admitted that the appropriation was their product. It is urgent for Muslim scientists to restore the glory of civilization to the glory of civilization of Islamic knowledge because it has been dormant for decades. All scientific movements that carry integrative education must start from Islamic Higher Education which is tasked with producing Muslim scholars who have strong faith and imtaq through the implementation of integrative education in the middle of Islamic campuses. The combination of curriculum based on the combination of general knowledge and religion. In fact, many have changed from institutes to universities, such as the State Islamic Religious Institute to become an Islamic University. This university policy is a concrete step in implementing integrative education at the higher education level as a form of participation by the academic community in the community.